The Effects of media tools on food consumption and obesity in adolescents - Kartal, Fatma; Rakıcıoğlu, Neslişah (Progress in Nutrition, 2020)
Purpose: The present study was aimed to define the quantities and types of foods consumed byadolescents during use of media tools to evaluate the contribution of energy and nutrient intake during theuse of media tools to daily energy and nutrient intake. Methods: A total of 73 adolescents who visits an internetcafe, were included in the study. Participants were evaluated when they were using a computer in aninternet cafe, food consumptions during the use of media tools and daily consumption and physical activitylevel were recorded. Results: It has been found that consumption of cakes, pastries and cookies during the useof media tools constitute more than half of daily consumption. At the same time, consumption of oily seeds,consumption of sweet foods and saturated fat consumption during the use of media tools were contributedto the daily consumption significantly. It was found that, adolescents consumed less egg, legumes, milk anddairy products, and vegetables in front of the media tools (p